Enhancing Integrated Competencies in Vocational Students Through Mechanical and Software Engineering Collaboration in the Era of Industry 4.0 - Stenli Octavian Eridheni; Januar Nur Rohmah Suprihartini; Systi Adi Rachmawati (Politeknik Mardira Indonesia, 2025)
The rapid development of digital technology in the era of Industry 4.0 demands multidisciplinary collaboration competence, especially between Mechanical Engineering and Software Engineering students in vocational education. However, the gap in digital literacy and automation skills among students still persists due to sectoral curricula, limited facilities, and minimal involvement of industry. This community service program aims to optimize interdisciplinary collaboration through technology-based knowledge transfer for vocational school students. The method consists of needs identification, coordination with partners, material preparation, training implementation, and evaluation. The activity was held at SMK PGRI Kandanghaur Indramayu, focusing on the introduction of programming, digital-based system modelling, and data presentation tools used in industrial environments. The results indicate increased students’ understanding of digital integration in mechanical systems and stronger motivation to pursue careers aligned with technological development. This initiative encourages the readiness of vocational education graduates to contribute to the transition toward Industry 4.0.